2005
DOI: 10.3102/00346543075001083
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Reading to Children Who Are Deaf: Do the Conclusions of the National Reading Panel Apply?

Abstract: The authors conducted a synthetic review of the research literature on the reading development and reading instruction of deaf students and compared their findings to the review of research literature conducted by the National Reading Panel (NRP) on four topic areas: (a) alphabetics (phonemic awareness instruction and phonics instruction); (b) fluency; (c) comprehension (vocabulary instruction and text comprehension instruction); and (d) computer technology and reading instruction. In their discussion of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
16

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 61 publications
(63 reference statements)
1
50
0
16
Order By: Relevance
“…'Self-generated questioning' is found as effective strategy for improving reading comprehension (Schirmer and McGough, 2005). However, it is not sufficient to just tell students to create their own questions but it is important to train them in how to create their own questions on the text which positively affect their understanding and recalling of information in the texts (Janssen, 2002).…”
Section: Scaffolding Through the Use Of Questioningmentioning
confidence: 99%
See 1 more Smart Citation
“…'Self-generated questioning' is found as effective strategy for improving reading comprehension (Schirmer and McGough, 2005). However, it is not sufficient to just tell students to create their own questions but it is important to train them in how to create their own questions on the text which positively affect their understanding and recalling of information in the texts (Janssen, 2002).…”
Section: Scaffolding Through the Use Of Questioningmentioning
confidence: 99%
“…Visualizing or "Mental Imagery" as described by Schirmer and McGough (2005) as a strategy that relies on forming mental images while reading. It involves "asking readers to construct a visual or spatial representation of what they are reading" (p.103).…”
Section: Scaffolding Through the Use Of Visualizingmentioning
confidence: 99%
“…This situation is thought to result from the fact that hearing impaired students require a longer period of time and more repetition in studies because of the limitations in their speech caused by hearing disabilities, and that they are unable to read a sufficient number of publications regarding professional language, added to factors concerning the quality of the education the students had received in the past. Research carried out on hearing impaired students also indicated that these students had difficulty in developing their vocabularies (Paul, 1996, Schirmer andMcGough, 2005; Trussell and Easterbrooks, 2016). It was determined that students gained more benefits from studies carried out with formal education than from the studies carried out on the internet.…”
Section: Effect Of the Applications On The Development Of Students' Vmentioning
confidence: 99%
“…However, more activities, repetition and revision strategies should be conducted and employed along with the combined usage of direct and indirect vocabulary instruction strategies (Karasu and Girgin, 2007;Luckner and Cooke, 2010;Paul, 1996;Schirmer and McGough, 2005). Nevertheless, individuals with hearing impairments acquire only a small amount of the vocabulary knowledge when indirect instruction strategies are used (Beck et al, 1983;Paul, 2001).…”
Section: Individual With Hearing Impairments and Vocabulary Developmentmentioning
confidence: 99%
See 1 more Smart Citation